PHYTOCHEMICAL TESTED AND IN VITRO SCREENING ANTI- MALARIA ACTIVITY OF BELILIK (Brucea javanica (L)). MERR AGAINST Plasmodium falciparum - Henny Helmi; Idha Susanti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
Screening of anti-malaria compound from nature is one of important thing to cure malaria disease especially in Bangka Belitung province. One of plant that as used as traditional medicine to cure malaria is Belilik (Brucea javanica (L.)Merr. The aim of this study was to investigate the present of some kind of biochemical compound, and to evaluate in vitro anti-malaria activity of ethanol extracts of Bruce javanica fruits and roots against Plasmodium falciparum. A visual method was allowed to evaluate the in vitro anti-malaria activity of the extracts against P. falciparum. The number of parasites per 5,000 erythrocytes on thin Giemsa stained smears was calculated microscopically. IC50 values were determined by probit analysis of SPSS 13 program. The result showed, that the ethanol extract of Belilik contained some biochemical compound such as alkaloid, flavonoid and phenol in fruits and alkaloid, phenol and saponin in roots. The anti-malaria activity of ethanol extracts of Brucea javanica fruits and roots on P. falciparum were very effective as IC50<0,01 μg/mL. The highest inhibition of 100 μg/mL of Brucea javanica fruits and roots were 5.95% and 16.99% respectively. Brucea javanica could inhibit Plasmodium falciparum in vitro with very small dosage of extract and very potential to develop as malaria medicine.